Prolonged myocardial protection during hypothermic storage: potential application for cardiac surgery and myocardial tissue engineering. (9th March 2018) - Beckmann, Erik; Kensah, George; Neumann, Anneke; Benecke, Nils; Martens, Andreas; Martin, Ulrich; Gruh, Ina; Haverich, Axel
Abstract: The increasing need for donor organs for heart transplantation and promising progress in myocardial tissue engineering requires more effective long-term storage strategies to provide adequate recipient supply and accelerate translation of novel strategies for myocardial regeneration and reconstruction. We designed a multi-segmental model to analyze the capability of different solutions to preserve cardiomyocytes, contractile engineered 3-dimensional myocardial tissue and whole hearts at hypothermia. Four chemically defined hypothermic storage media and two clinical cardioplegic solutions were compared in standardized hypothermia-reperfusion protocols. We identified an animal-free and chemically defined solution (ChillProtec), not yet in clinical use, that attenuated hypothermic ischemia-reperfusion injury of single cardiomyocytes and multicellular myocardial tissue constructs significantly. Stored for up to five days in hypothermic conditions (4 °C–8 °C), cardiomyocytes showed significantly less cell death and maintained physiological function, i.e. contractility and force development, which was in part prevented by cell swelling and inhibition of apopotosis. In an ex vivo -model mimicking clinical situations, we were able to preserve adequate function in Langendorff-perfused isolated rat hearts after hypothermic storage. Our findings have direct implications on both in vitro and pre-clinical in vivo studies on novel regenerative strategies involving cardiomyocytes, such as drug development and reconstructive cell therapies. Moreover, the prolonged biopreservation described here may serve as basis to further optimize hypothermia-associated routines for cardiac surgery concerning intra-operative cardioplegic arrest or organ preservation for transport and extended storage.